Participatory arts and affective engagement with climate change: The missing link in achieving climate compatible behaviour change?. (March 2018) - Burke, Miriam; Ockwell, David; Whitmarsh, Lorraine
Highlights: Participatory arts might hold key to climate compatible behaviour change. Arts based interventions must be combined with interpretive social science. Value demonstrated by application to small sample in Outer Hebrides, Scotland. Provides basis for new research & policy agenda across arts and social sciences. Abstract: Despite a growing number of arts based climate change interventions and the importance emphasised in the social psychology literature of achieving affective (emotional) engagement with climate change before climate compatible behaviour change is likely, to date there has been no systematic application of interpretive social science techniques to understand the ways in which these arts based interventions do or do not achieve affective public engagement with climate change and hence might hold the key to unlocking broader climate compatible behaviour change. This article makes two key contributions. First, it analyses the literature across social psychology and participatory arts to demonstrate why participatory, climate change based arts interventions could hold the key to more effective approaches to engaging multiple publics in climate compatible behaviour change. Second, using a small sample of participants in an arts based climate change intervention in the Inner Hebrides, Scotland, it demonstrates the potential value of combining social science techniques (in this case Q Methodology) with participatory arts interventions to better understand and learn from the ways in which climate based arts interventions achieve affective public engagement with climate change. This raises the potential for a significant new research and policy agenda looking forward.